PENGARUH VARIABEL MAKRO EKONOMI TERHADAP KREDIT PERBANKAN - Cep Jandi Anwar (FEB Universitas Sultan Ageng Tirtayasa, 2016)
Abstract The aims of this research is to study the influence of narrow money, BI Rate and Inflation on Banking Credit of Indonesian Public Banking. Those are macroeconomic variables which have close relationship and significant effect on banking credit. Methodology in this research used quarterly period on Statistic Indonesian Banking data issued by Bank Indonesia, from January 2006 to April 2014. Methodology in this research is Ordinary Least Square. We used this methodology since it fit on this research.Finding in this research are narrow money and inflation have positif and significant effect on banking credit, whereas BI Rate has negatif and significant effect on banking credit. Those results are appropriate with theory and previous studies. Inflation creates increasing in resources cost in a companyas a result demand for credit will climb. On the other hand, if Bank Indonesia increase BI Rate, thus will be responded by commercial banks with rise their credit interest rate, consequently demand for credit will decrease.Keywords : Broad Money, BI Rate, Inflation and Banking Credit